Hydrophobic and oleophobic sol‐gel coatings on glass substrates for usage at high temperatures. (2nd April 2018) - Özmen, Eren; Durán, Alicia; Castro, Yolanda
Abstract: The paper reports an optimized process to obtain transparent and highly hydrophobic sol‐gel coatings with further oleophobic behavior at high temperatures. Polyorganosiloxane sols were prepared incorporating an organic based precursor, 1 H, 1 H, 2 H, 2 H Perfluorooctyltriethoxysilane (POTS), into a silica‐based hybrid sol and deposited on soda‐lime glass‐slides. The coating surfaces show high water contact angle (WCA) around 120 ± 1° and oil contact angle (OCA) of 70 ± 1° after curing at temperatures between 350 and 400°C. The coatings thickness changed between 300 and 2000 nm depending on sol composition and curing temperature. Easy‐to‐clean tests were performed, the results showing excellent anti‐stick and easy‐to‐clean properties compared to non‐coated samples. Atomic force microscopy (AFM) revealed the presence of rippled surfaces with morphology similar to "lotus leaf surface, " this explaining the properties. These hybrid fluoroalkylsilane sol‐gel coatings are a good alternative to provide anti‐stick and easy‐to‐clean properties to glass substrates being quite easy to scale up.